Melhoria da competitividade de preço de uma PME do Polo Industrial de Manaus através da aplicação das ferramentas de Lean Manufacturing: uma abordagem entre cliente e fornecedor - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This work presents a research of practical application of Lean Manufacturing tools in a small company of the Industrial Pole of Manaus that supplies metallic stamping products to a multinational motorcycle manufacturer. The problem encountered is the lack of structured work to reduce waste at the parts supplier, given a scenario of retraction in motorcycle sales. Therefore, the objective of the research is to use Lean Manufacturing tools to improve the price competitiveness of the supplier of stamped metallic products in the motorcycle segment of the Manaus Industrial Pole. For this, a bibliographic review was carried out around the principles of Lean Manufacturing, as well as the processes of stamping and welding, in addition an exploratory research was carried out. The main results achieved were the absorption of knowledge of the Lean tools used in the research, which enabled the generation of activities that contributed to the reduction of waste in the analyzed processes, in addition to the establishment of an approach for negotiation between customer and supplier.
Keywords: Lean Manufacturing; Lean Supply Chain; Administração da produção; Polo Industrial de Manaus; Cultura de resultados enxutos; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO; Lean Manufacturing; Lean Supply Chain; Gestão da Produção